Biological treatment of biowaste as an innovative source of CO—The role of composting process - Sobieraj, Karolina; Stegenta-Dąbrowska, Sylwia; Luo, Gang; Koziel, Jacek A.; Białowiec, Andrzej (Frontiers in Bioengineering and Biotechnology, 2023)
The demand for biowaste treatment processes continues to grow worldwide, both in terms of the total mass and types of bio-waste subjected to treatments. New technologies are needed for the disposal of biomass waste and and resource recovery. Carbon monoxide (CO) is an essential ‘building block’ for producing everyday chemicals on industrial scale. CO can also be generated though a lesser-known and sometimes forgotten biorenewable pathways that could be explored to advance biobased production from large and more sustainable sources such as bio-waste composting. Organic matter decomposition can generate CO both under aerobic and anaerobic conditions. While anaerobic CO generation is relatively well understood, the aerobic is not. Yet many industrial-scale bioprocesses involve both conditions. This review summarizes the necessary basic biochemistry knowledge needed for realization of initial steps towards biobased CO production. The limited information about CO sources, mechanisms, microorganisms involved, and optimal conditions for its formation during bio-waste aerobic biostabilization, including composting, is summarized. We analyzed for the first time, the complex information about CO production during aerobic, anaerobic bio-waste treatment and storage, CO-metabolizing microorganisms, pathways, and enzymes with bibliometric analysis of trends. Specific focus is placed on the role of carbon monoxide hydrogenase (CODH) activity as the controlling agent for the net CO production, and further transformation into H2. The future directions recognizing limitations of combined composting and CO production have been discussed in greater detail. This review summarizes the necessary basic biochemistry knowledge needed for realization of initial steps towards biobased CO production and biohydrogen economy.